Pemanfaatan Google Drive sebagai Layanan Cloud Computing untuk Penyimpanan Kolaborasi Data - Fitrian, Harry Pribadi; Kusdiawati, Indah; Rendi Rohman Nursoleh; Rizal Ramdani; Ahmad Rois (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The use of Google Drive as a cloud computing service has brought about significant changes in the way users store, manage, and collaborate on data. As a Software as a Service (SaaS) service, Google Drive offers easy access, flexibility, and efficiency in internet-based storage. Users can upload, manage, and share various files via the 15 GB of free storage provided by Google. The real-time collaboration feature makes it easy for multiple people to work together on a single document, supporting coordination in education, work, and organizations. Furthermore, Google Drive's integration with other Google services such as Google Docs, Gmail, and Google Photos further enhances user productivity. Various benefits, such as document translation, PDF-to-text conversion, file backup, link storage, and WhatsApp chat backup, make this platform a complete digital storage solution. However, despite this convenience, security remains a major concern. The risk of data leaks, unauthorized access, and phishing attacks can occur if users do not properly understand privacy settings and access permissions. Therefore, digital literacy regarding cloud security needs to be improved. Overall, Google Drive plays a crucial role as a cloud computing service that supports efficient data storage and collaboration. When used properly, this platform can improve work effectiveness, accelerate information sharing, and support data management in the digital age.